A Review of the Implementation of an Online Registration System to Support Waiting Time Efficiency at RSUD Bandung Kiwari - Aprilianti, Sofi; Gunawan, Erix (MultiTech Publisher, 2024)
A Hospital is an institution that organizes health services in full including outpatient services. This study aims to review the implementation of an online registration system to overcome the problem of waiting time for outpatients at Bandung Kiwari Hospital. The research method used was descriptive quantitative analysis with 22 respondents aged 20-45 years. Primary data was collected through questionnaires, while secondary data was obtained from direct observation. The results showed that 85.2% of respondents agreed with online registration as part of the digitalization of hospital services. Observation revealed an average service time of 3,590 minutes, equivalent to 2 hours and 4 minutes. The main problems found were patients who had made online reservations did not come as scheduled and the lack of patient understanding of the online registration flow. In addition, management elements also play a role in patient service. It can be concluded that the implementation of the online registration system is quite effective in overcoming the problem of waiting time, but requires improvement in socialization and coordination with patients.